Partial Response After Toripalimab Plus Anlotinib for Advanced Metaplastic Breast Carcinoma: A Case Report - Fu, Yang; Liu, Jie; Jiang, Yu (Frontiers in Endocrinology, 2022)
Metaplastic breast carcinoma (MBC) is an aggressive subtype of breast cancer, accounting for <1%. The clinical outcome is unknown due to the lack of treatment options. Here, we present the case of a 58-year-old woman with advanced MBC, in which standard adjuvant chemotherapy was unsuccessful. In the second-line therapy, she received anti-angiogenic(anlotinib) therapy plus chemotherapy. Finally, she was subsequently treated with immunotherapy (toripalimab) combined anlotinib and achieved partial response (PR); thus, immunotherapy plus anti-angiogenic therapy might be a novel option for advanced MBC patients.